First approach to the growth and age corroboration of Northeast Atlantic chub mackerel (Scomber colias) in Northern Iberian waters. (30th September 2021) - Navarro, M.R.; Landa, J.; Villamor, B.; Domínguez-Petit, R.
Abstract: The growth pattern and parameters of Atlantic chub mackerel in Northern Iberian waters were analysed for the first time in this study, using otolith analyses (direct age estimation-DAE, back-calculation-BC and otolith marginal analyses) and length frequency analyses (Bhattacharya, SLCA and PROJMAT methods), on a time series of data from 2011 to 2017. Two main different growth patterns were obtained, one slower (DAE, BC and PROJMAT) and other faster (Bhattacharya and SLCA). Otolith marginal analyses showed an annual periodicity in the formation of one hyaline and one opaque edge, with a prevalence of the opaque edge from June to December, what in addition to the unimodal distribution of the annuli radii and the obtained back-calculated mean lengths, similar to those obtained by DAE, support the age estimation criteria used here. The growth parameters obtained from DAE ( L ∞ : 45.34, k: 0.28, t 0 : -1.18 ) are proposed for the upcoming stock assessment process. Graphical abstract: Image 1 Highlights: Growth study of Atlantic chub mackerel in north Iberian waters using different approaches. Otolith marginal analysis showed annual periodicity in the annuli deposition. Back-calculation and annuli radii distribution supported the age estimation criteria used. Length frequency analyses resulted in higher growth rates than otolith age estimation. Growth parameters estimations available for upcoming stock assessment.